Soil Moisture and Soil Depth Retrieval Using the Coupled Phase-Amplitude Behavior of C-Band Radar Backscatter in the Presence of Sub-Surface Scattering. Issue 6 (2nd November 2022) - Morrison, Keith; Wagner, Wolfgang
Abstract: In low-moisture regimes, strongly-reflecting bedrock underlying soil could provide a dominant return. This offers a novel opportunity to retrieve both the volumetric moisture fraction ( mv ) and depth ( d ) of a soil layer using a differential phase. A radar wave traversing the overlying soil slows in response to moisture state; moisture dynamics are thus recorded as variations in travel time—captured back at a radar platform as changes in phase. The Phase Scaled Dielectric (PSD) model introduced here converts phase changes to those in soil dielectric as an intermediate step to estimating mv . Simulations utilizing a real soil moisture timeseries from a site in Sudan were used to demonstrate the linked behaviors of the soil and radar variables, and detail the PSD principle. A laboratory validation used soil with a wet top layer variable in depth 1–2 cm and drying from mv  ∼ 0.2 m 3 m −3, overlying a gravel layer at a depth of 11 cm. The scheme retrieved d  = 1.49 ± 0.33 cm and a change Δ mv  = 0.191–0.021 ± 0.009 m 3 m −3 . The PSD scheme outlined here promises a new avenue for the diagnostic measurement of soil parameters which is not currently available to radar remote sensing.